Hysterectomy alone vs. hysterectomy plus sentinel node mapping in endometrial cancer: Perioperative and long-term results from a propensity-score based study. Issue 5 (May 2023) - Bogani, Giorgio; Di Donato, Violante; Papadia, Andrea; Buda, Alessandro; Casarin, Jvan; Multinu, Francesco; Plotti, Francesco; Gasparri, Maria Luisa; Pinelli, Ciro; Perrone, Anna Myriam; Ferrero, Simone; Sorbi, Flavia; et al.
Abstract: Objective: To compare outcomes after hysterectomy and hysterectomy plus sentinel node mapping (SNM) in endometrial cancer (EC) patients. Materials and methods: This is a retrospective study, collecting data of EC patients treated between 2006 and 2016 in nine referral centers. Results: The study population included 398 (69.5%) and 174 (30.5%) patients having hysterectomy and hysterectomy plus SNM. As the results of the adoption of a propensity-score matched analysis, we selected two homogeneous cohort of patients (150 having hysterectomy only vs. 150 having hysterectomy plus SNM). The SNM group had a longer operative time, but did not correlate with length of hospital stay and estimated blood loss. Overall severe complication rates were similar between groups (0.7% in the hysterectomy group vs. 1.3% in the hysterectomy plus SNM group; p = 0.561). No lymphatic-specific complication occurred. Overall, 12.6% of patients having SNM were diagnosed with disease harboring in their lymph nodes. Adjuvant therapy administration rate was similar between groups. Considering patients having SNM, 4% of patients received adjuvant therapy on the basis of nodal status alone; all the other patients received adjuvant therapy also on the basis of uterine risk factors. Five-year disease-free (p = 0.720) and overall (p = 0.632) survival was not influenced by surgical approach. Conclusions: Hysterectomy (with or without SNM) is a safe and effective method for managing EC patients. Potentially, these data support the omission of side specific lymphadenectomy in case of unsuccessful mapping. Further evidence is warranted in to confirm the role SNM in the era of molecular/genomic profiling. Highlights: Sentinel node mapping (SNM) is accurate in identifying disease harboring in the lymph nodes in EC. In comparison to hysterectomy only, the addiction of SNM does not increase morbidity rate. The omission of retroperitoneal staging has no negative effect on influencing oncologic outcomes. Recent advances in molecular studies have refined the prognosis for EC and uterine risk factors are the main variable influencing the need of adjuvant therapies. In few EC patients (merely 4%) nodal status is the only factor used in determining appropriate adjuvant therapy.